Effect of Plane of Nutrition on Blood Biochemical Profile and Reproductive Efficiency in Nili Ravi Buffalo Heifers
Fifteen Nili Ravi heifers aged I 3 months were randomly divided into three groups of 5 each. Group-I was fed I 00%, Group-II II 5% and Group-II1 130% of nutrients as per the Kearl (1982) feeding standards. Blood samples were collected at fortnightly intervals. Haemoglobin and haematocrit did not differ significantly in the three groups. Blood glucose levels in Groups I, II and Ill were 70.15± 1.67, 67.15± 1.67 and 65.25± 1.67 mg %, respectively. The differences were significant P<0.05) in Groups I and Ill. Protein values did not differ significantly among the groups. Plasma urea (mmol/1) was higher in Group-I (7.38±0.34) followed ,by Group-II (6.85±0.34) and Group-III (6.18±0.34). The differences in Group-I and Group-III wer:e ;Jgnificant P<0.05). Similarly, cholesterol (mg%) was higlwr (P<0.05) in Group-I (64.64±3.01) followed .by Group-II (61.38±3.01) and Group-III (52.88±3.01). Plasma triglycerides and thyroxine did not differ significantly among the groups. Plasma triiodothyronine (ng/ml) was highest in Group-I (1.67±0.07) followed by’ Group-II (1.54±0.07) and Group-III (1.39±0.07). The differences were significant (P<0.05) in Group-I and Group-III.Age at puberty (days) was lowest in ’Group-III (801.80±46.70) followed by Group-I (828.00±46.70) and Group-II (834.80±46.70). Significantly lower age at sexual maturity (days) was recorded in Group-II (840.40±54.24) fot.l Wed: by Group-I (828.00±46.70) and Group-III (1067.00±54.24). Number of services per conception lowest in Group-II (1.20±0.50) followed by Group-I (2.70±0.50) and Group-III (3.00±0.50). It can be concluded · that feeding the Nili Ravi heifers at 115 and 130% depressed circulating plasma levels of glucose, urea, cholesterol and T3 Reproductive efficiency in terms of age at sexual maturity and services per conception was highest at 115% plane of nutrition. , number=2, journal=The Indian Journal of Animal Reproduction, author=MAVI, P S and BAHGA, C S and SINGH, NARINDER and NAYYER, SHASHI, year=2023, month=Feb., pages=133–137